The Role of Law in Rice Scarcity Mitigation - Soetopo, Maria G.S. (Journal of Law, Politic and Humanities, 2025)
In support of national food security, the government issued Presidential Instruction No. 6 year 2025 concerning the Procurement and Management of Domestic Grain/Rice and the Distribution of Government Rice Reserves (Presidential Instruction No. 6 year 2025). However, Indonesia continues to face rice scarcity and rising prices due to policy inefficiencies. In fact, the government has issued various policies to ensure the availability and affordability of rice prices in the community. This article evaluates the authority of Ministries and Institutions in making policies to mitigate rice scarcity. This article uses normative legal research methods supported by economic analysis. The results of the study show that there is a lack of institutional coordination that results in society’s reduced purchasing power.